P047: Understanding the expert approach to managing frailty in the emergency department. (May 2019) - Forrester, S.; Nelson, M.; McLeod, S.; Melady, D.
Abstract : Introduction : Frailty is a state of vulnerability affecting older adults, and has been associated with adverse events such as increased risk of institutionalization, falls, functional decline, and mortality. Previous research suggests that emergency department (ED) physicians are much less comfortable managing the complex care needs of frail, older adults. The objective of this study was to identify successful strategies and expert skills that ED physicians possess to optimally manage the frail, older patient.Methods : An interpretive descriptive qualitative study was conducted. One of the investigators contacted the site leads of 12 academic and community EDs across Canada to identify ED physicians who they perceived as being highly skilled in the care of frail, older patients. 22 individual physicians were identified and 13 physicians representing 10 EDs were invited to participate in a 30-minute semi-structured interview. Transcripts were coded by two members of the research team. Data collection is ongoing and analyses will occur until thematic saturation.Results : All participants indicated they were very comfortable managing the frail, older patient in the ED. Awareness of issues related to this patient population were triggered by both clinical and personal experiences, as well as institutional priorities. When asked how they developed their specific skills for this patient population, participants stated they received limited formal training during residency and early practise, but relied on situational learning, access to role models and engagement in self-directed learning. Participants identified three predominant management strategies for the care of the frail, older patient: thorough patient interaction at the start of the clinical encounter to maximize efficiency; engaging in teamwork to manage complex issues; and early involvement of the family/caregivers. Interestingly, not all participants used the term frailty, however most reflected principles of the concept in their discussion.Conclusion : Currently, principles of caring for frail, older adults are not widespread in emergency medicine residency training. These findings suggest that frailty care frequently requires an alternative clinical approach, which is often derived from personal experience, self-directed and experiential learning. Future educational initiatives should derive, implement and evaluate a wide-spread curriculum to teach the skills required to optimally care for these patients.